AKTIVITAS SITOTOKSIK EKSTRAK ETANOLIK HERBA CIPLUKAN (Physalis angulata L.) PADA SEL KANKER LEHER RAHIM HeLa MELALUI MODULASI EKSPRESI PROTEIN p53 - Darma, Andita Pra; Ashari, Rosana Anna; Nugroho, Perdana Adhi; Monikawati, Ameilinda; Fauzi, Ilham Agusta; Hermawan, Adam; Meiyanto, Edy (University of Muhammadiyah Malang, 2011)
Cervical cancer is one of leading cause of cancer death in women in the developing countries. One of the strategy to prevent cervical cancer based on cytotoxic agents are now being developed. Ciplukan (Physalis angulata L.) is one of potential plant as chemopreventive agent due to Physalin and Withangulatin constituent in this plant. This study was aimed to know cytotoxic effectÂ of ciplukan ethanolic extract (CEE) in human cervical carcinoma Hela cell line. Evaluation of cell viability value was determined using MTT assay. The expression of p53 as cell proliferation regulator was observed with immunocytochemistry assay. Ethanolic extract of ciplukan showed cytotoxic effect in HeLa cell line with IC50 of 158 Âµg/ml. Further observation of cell proliferation regulator showed that CEE induces expression of p53 that inhibit cell proliferation. The result showed that CEE has potential activity to be developed as anticancer agent in human cervical cancer.